2011
DOI: 10.1111/j.1439-0426.2011.01711.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of anaesthetics MS-222 and clove oil on blood biochemical parameters of juvenile Siberian sturgeon (Acipenser baerii)

Abstract: The effects of MS-222 and clove oil on blood biochemical parameters of juvenile Siberian sturgeon (Acipenser baerii) were studied. MS-222 caused higher glucose (GLU) concentrations in anaesthetic test groups than for the control group. Triglyceride (TGL) concentrations of fish in the 140 and 160 mg L )1 groups were also significantly higher than those of other groups. Alanine aminotransferase (ALT) activity in the 140 mg L )1 group was significantly higher than the level in 80, 100 and 120 mg L )1 groups. Aspa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
39
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(41 citation statements)
references
References 37 publications
2
39
0
Order By: Relevance
“…In this study four different group of anesthetics to carp are investigated from the point of view use as an anaesthetizing baths. One of the most widely used anesthetic agents for fish is clove oil, which is readily available, low cost, without prescription and no risk to human health [2]. Our results about clove oil properties such as time of induction and recovery were the same as those described by a number of researchers [11,7,12] and its advantages such as increased safety for fish compared to other immersion drugs [13].…”
Section: Resultssupporting
confidence: 76%
See 1 more Smart Citation
“…In this study four different group of anesthetics to carp are investigated from the point of view use as an anaesthetizing baths. One of the most widely used anesthetic agents for fish is clove oil, which is readily available, low cost, without prescription and no risk to human health [2]. Our results about clove oil properties such as time of induction and recovery were the same as those described by a number of researchers [11,7,12] and its advantages such as increased safety for fish compared to other immersion drugs [13].…”
Section: Resultssupporting
confidence: 76%
“…[1,2,3,4,5]. The most widely method for administration of anesthetics who is analogous to gaseous anesthesia is water-borne anesthesia [6].…”
Section: Introduction mentioning
confidence: 99%
“…Thus, it is of high necessity to establish appropriate anaesthetic concentration to minimize stress (see Feng, Zhuang, Zhang, Kynard, Shi, Liu & Huang 2011). Thus, it is of high necessity to establish appropriate anaesthetic concentration to minimize stress (see Feng, Zhuang, Zhang, Kynard, Shi, Liu & Huang 2011).…”
Section: Resultsmentioning
confidence: 99%
“…A previous study found that prolonged handling, analogous to the 24‐hour period that Sturgeon in this study were in the gill nets, resulted in broader intervals for serum analytes than in minimally restrained Adriatic Sturgeon ( Acipenser naccarii ) . Because fish were returned to the river immediately after sampling, and venipuncture in manually restrained Sturgeon has been previously described as a minimally invasive procedure, we chose not to use anesthetics to avoid confounding of intervals, Interestingly, the RIs we report here for values that have reportedly been affected by stress (PCV, sodium and chloride concentrations, and others) are similar to RIs previously reported in anesthetized Sturgeon …”
Section: Discussionmentioning
confidence: 96%
“…However, the lack of published RIs has prevented the widespread use of these important tools. In addition, many studies have documented the effects of a variety of environmental and physiologic factors, including seasonality, water salinity, temperature and oxygen content, age and sex of the fish, and influence of the use of anesthetics on hematologic and biochemical analytes in fish, thus further complicating a scientifically sound interpretation of these variables . Here, we report hematologic and plasma biochemical values from manually restrained, wild adult Lake Sturgeon.…”
Section: Discussionmentioning
confidence: 96%